Experience with Rectangular Titanium Cages in Anterior Cervical Discectomy and Fusion in a Single Unit of a Tertiary Level Hospital, Dhaka. - Islam, Md Joynul; Ashadullah, ATM; Elahy, Fazle; Uddin, Kazi Hafiz; Ahmad, Misbah Uddin; Mondle, Md Shamsuzzaman; Ali, Md Masum; Saha, Sanat Kumar; Asfia, Kazi Nur; Rashid, Mirza Md Hafizur (Bangladesh Journal of Neurosurgery, 2021)
Background: Anterior cervical discectomy is a common procedure for treating patients for cervical disc prolapse. This study was conducted to evaluate the surgical outcome and demographic characteristics of patients who were treated for anterior cervical disc prolapse. Methods: Study was conducted in the Department of Neurosurgery-spine, National Institute of Neurosciences and Hospital, Dhaka. Study interval was 5 years from January, 2014 to 31st December, 2019. Total numbers of patients were 215. Males were 183 (85.1%) and females were 32 (14.9%). All the patients had undergone the procedure of anterior cervical discectomy and fusion (ACDF) with RABEA Rectangular Titanium Cages (RTC). All the patients had plain MRI cervical spine done for diagnosis of anterior cervical disc prolapse. Surgical and Clinical preoperative evaluation and surgical outcomes were evaluated using pre- and postoperative Nurick, Visual Analog Scale (VAS), Neck Disability Index (NDI), for Myelopathy, overall Odoms outcome scores, postoperative surgical complications, and fusion and subsidence rates. Results: Total 215 patients underwent ACDF; the mean age of these patients was 44.66 years, and their preoperative VAS and NDI, scores were 8.09 and 35.38 respectively. Sixty seven percent of patients had one level, 25.1% had two-level, and 7.9% had three-level procedures. On preoperative Magnetic Resonance Imaging(MRI), foraminal stenosis was present in 68.4% of patients, whereas medullar stenosis was present in 43.7%. The rate of complications was 2.8%: two patients had postoperative implant migration (0.93%), three patients had postoperative transient dysphagia (1.4%) and one patients had temporary hoarseness of voice. Mean postoperative follow-up time was 6.7 months; postoperative VAS and NDI scores were 1.10 and 14.4, respectively. Postoperative fusion rate was 93.5%, and subsidence rate was 5.6%. Conclusion: Results with Rectangular Titanium Cages are expectedly good. Symptoms resolved and fusion rate was 93.5% at 1 year follow up. Bang. J Neurosurgery 2021; 10(2): 137-147